Diversity of dragonfly larvae in some parts of northern Thailand: Diversity of dragonfly larvae in some parts of northern Thailand - Phattanarak, Chatayathon; Boonsoong, Boonsatien (Agriculture & Technology RMUTI Journal, 2024)
Diversity of dragonfly larvae (Order Odonata, Suborder Anisoptera) were investigated at stream and wadeable river of Chiang Mai, Nan and Chiang Rai provinces. Eighteen sampling sites were sampled during October 2020 to March 2021. Dragonfly larvae were collected using D-frame net and fully-grown larvae were reared in laboratory. Unidentified larvae were associated using DNA barcoding (COI). A total of 291 specimens of dragonfly larvae were identified into 23 species, 17 genera and 5 families (Aeshnidae, Gomphidae, Libellulidae, Macromiidae and Synthemistidae). The family Gomphidae (13 species) is the most diverse species richness followed by Libellulidae and Aeshnidae, respectively. The association of larvae and adult succeed in 3 species (Idionyx selysi, Paragomphus capriconis and Tetracanthagyna plagiata). The similarity analysis (Blastn) found that 3 species which Heliogomphus selysi, Pantala flvescens and Trithemis festiva presented in GenBank and BOLD database. Principal Component Analysis (PCA) analysis revealed that dragonfly larvae were correlated with each provincial region, which Megalogomphus sp., Stylogomphus sp. and Idionyx sp. associated with Chiang Rai Province. Undisturbed and headwater stream sites scatter more than disturbed and wadeable river sites.